2022
DOI: 10.21037/acs-2022-bav-22
|View full text |Cite
|
Sign up to set email alerts
|

Procedural and clinical outcomes of transcatheter aortic valve replacement in bicuspid aortic valve patients: a systematic review and meta-analysis

Abstract: Background: Currently, bicuspid aortic valve (BAV) anatomy remains a relative contraindication for transcatheter aortic valve replacement (TAVR) due to concerns of suboptimal anatomy. However, recent advancements in the field have provided a wealth of promising data and more clinicians are opting for TAVR as an alternative to surgical repair. We aim to review and analyze the available data for TAVR in BAV patients, targeting procedural outcomes, clinical outcomes and mortality with up to two years of follow-up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 70 publications
1
4
0
Order By: Relevance
“…In the patient presented, a bicuspid aortic valve could have also contributed to DCO. A study of bicuspid aortic valve patients found the incidence of DCO after TAVR to be 0.1%, similar to that found in other studies including both bicuspid and tricuspid valve patients [ 15 ]. However, it has been shown that bicuspid aortic valves have a higher calcium burden compared to tricuspid valves [ 16 ].…”
Section: Discussionsupporting
confidence: 84%
“…In the patient presented, a bicuspid aortic valve could have also contributed to DCO. A study of bicuspid aortic valve patients found the incidence of DCO after TAVR to be 0.1%, similar to that found in other studies including both bicuspid and tricuspid valve patients [ 15 ]. However, it has been shown that bicuspid aortic valves have a higher calcium burden compared to tricuspid valves [ 16 ].…”
Section: Discussionsupporting
confidence: 84%
“…Indeed, multicentre registries reported more favorable outcomes with the implementation of newer generation devices (Medtronic CoreValve Evolut R/PRO and Edwards Sapien 3), albeit in relatively small cohorts 13,14 . More contemporary evidence is obtained in terms of midterm clinical FU reporting the survival rate at 1 or 2 years 15 . Recently, Zhou et al compared 109 BAV with 137 TAV treated with TAVI reporting a similar 3‐year survival rate between two groups (87.1% vs. 79.5%, respectively, log‐rank p = 0.126) 16 .…”
Section: Discussionmentioning
confidence: 99%
“…13,14 More contemporary evidence is obtained in terms of midterm clinical FU reporting the survival rate at 1 or 2 years. 15 Recently, Zhou et al compared 109 BAV with 137 TAV treated with TAVI reporting a similar 3-year survival rate between two groups (87.1% vs. 79.5%, respectively, log-rank p = 0.126). 16 Recently published results from the BIVOLUTX registry demonstrated the favorable performance of Evolut PRO and Evolut R TAVI in patients with BAV anatomy.…”
Section: Clinical Outcomesmentioning
confidence: 95%
“…Nonetheless, there remains a shortage of conclusive evidence regarding coronary and commissural alignment, as well as coronary access following TAVR in cases involving bicuspid valves. However, studies centred around bicuspid valves available in the literature suggest that TAVR can be effectively and safely performed with a quite low risk of coronary occlusion in such valve types [ 78 , 79 , 80 ]. Moreover, TAVR might serve as a viable alternative for individuals with bicuspid valves who are deemed unsuitable candidates for traditional surgical approaches [ 78 , 79 , 80 ].…”
Section: Bicuspid Aortic Valve Clinical Management In Current Aortic ...mentioning
confidence: 99%
“…However, studies centred around bicuspid valves available in the literature suggest that TAVR can be effectively and safely performed with a quite low risk of coronary occlusion in such valve types [ 78 , 79 , 80 ]. Moreover, TAVR might serve as a viable alternative for individuals with bicuspid valves who are deemed unsuitable candidates for traditional surgical approaches [ 78 , 79 , 80 ]. Notably, the 2020 ACC/AHA Guideline for the Management of Patients with Valvular Heart Disease [ 68 ] designates TAVR as a class IIb recommendation, level of evidence B, under specific conditions for bicuspid patients.…”
Section: Bicuspid Aortic Valve Clinical Management In Current Aortic ...mentioning
confidence: 99%